Lessons learnt from a leadership and service development project to reduce laboratory expenditure in George Regional Hospital, South Africa - Jamie Arberry; Tian Koen; Louis Jenkins (Future Healthcare Journal)
Healthcare facilities globally are under pressure to ensure rational resource allocation. Hospitals across South Africa are already under significant strain so identifying areas where expenditure can be reduced requires detailed analysis and innovation. We conducted a service development project in George Hospital, South Africa. The project was implemented through a leadership development programme, funded by NHS England, and involved collaboration between a UK doctor, and senior staff at George Hospital. The aim was a reduction in expenditure on laboratory investigations, as over-utilisation of laboratory tests occurs among 20.6% of all tests.1 To reduce over-utilisation, evidence from hospitals in South Africa and globally suggest many methods, including unbundling test panels,2-4 increasing cost awareness2,4,5 and regular teaching and feedback.3,4To understand existing attitudes and identify areas for improvement, staff interviews were conducted and laboratory expenditure analysed. A literature review was conducted, and then a Plan-Do-Study-Act (PDSA) methodology was utilised. Data was captured using run charts with statistical process control lines.The interventions were sequentially undertaken in a PDSA fashion and included unbundling of laboratory tests, increased use of point-of-care testing, frequent training sessions, individualised feedback for each department, distribution of ‘cost-of-test’ resources, and engagement of the heads of each clinical department. Clinician awareness of laboratory costs increased by 29%. Savings of up to 28% were made in the emergency centre (the highest spending department) compared to the same time period in the previous year. This produced savings of up to 19% across the whole hospital compared to the same time period in the previous year (see figures 1 and 2). The service development project has demonstrated sustainability as costs have stayed down since the completion of the project, and ongoing monitoring and engagement is vital for sustained impact.The significantly higher savings in the emergency centre compared to other departments around the hospital may be due to strategic intervention here, the presence of the blood gas machine or due to strong clinical leadership and engagement from the heads of the department.This service development project provided reciprocal learning for individuals on both sides of this partnership, including the reinforcement of QI methodology, teamwork skills and leadership skills. It demonstrates how the use of multiple PDSA cycles can result in significant and sustainable change in expenditure. This study also highlights the value of global workforce development partnerships involving multi-directional healthcare worker learning and development exchange.